PENGARUH EVENT MARKETING TERHADAP MINAT BERKUNJUNG DI CIBINONG CITY MALL - Osta Nababan, Benny; Ayu Ningsih, Septia (Economicus, 2022)
This study aims to determine the effect of event marketing (involvement, interaction, immersion, intensity, individuality, innovation, and integrity) on interest in visiting Cibinong City Mall, to find out what factors are the most dominant in influencing interest in Cibinong City Mall and to knowing the magnitude of the determination of event marketing variables in explaining interest in visiting Cibinong City Mall. Based on the results of the study, it was found that the variables involvement, interaction, immersion and integrity had a positive and significant influence on visiting interest. Meanwhile, the variables of intensity, individuality and innovation have no effect on interest in visiting Cibinong City Mall. Simultaneously, all independent variables have a positive and significant influence on visiting interest. The for the amount of determination, the results were 34,7%, meaning that the variable of interest in visiting was influenced by event marketing variabels (involvement, interaction, immersion, intensity, individuality, innovation, and integrity) of 34,7% while the rest was 65.3% influenced by other variables not examined in this study.